(untitled) (Research, Society and Development, 2021)
In this study, two silica xerogels were synthesized by sol-gel method using an acidic aqueous solution and a basic aqueous solution as catalysts for each material, named as SiO2-A and SiO2-B, respectively. Dyes, such as methylene blue (MB), are common contaminants present in wastewater from textile industries and the search for or improvement of processes capable of reducing these damages by retention these pollutants is extremely important. These xerogels were used as adsorbent for removing methylene blue (MB) from aqueous solutions. Ultra-Violet visible spectroscopy was used to monitor the adsorption process. The porosity and morphology of these xerogels were studied by using N2 adsorption and desorption isotherms and scanning electron microscopy (SEM), respectively. The experimental data showed that the MB adsorption is higher at pH 9,0 for both xerogels, with a high performance for the SiO2-B xerogel. These results best fitted to Langmuir isotherm model, attaining values of maximum adsorption mass of 50,6 mg g-1 and 8,24 mg g-1 of MB for the SiO2-B and SiO2-A, respectively. The SEM images show that the SiO2-A has a smooth surface, while the SiO2 B has a rough morphology with agglomerates. The porosity data show these xerogels are mesoporous. Our experiments demonstrated that the SiO2-A and SiO2-B xerogels could be used in environmental applications to removal of water pollutants such as dyes.